Association of Angiogenic Cells in the Tumour Microenvironment and the Circulating Matured Endothelial Cells in Astrocytic Glioma - Das, Priscilla; Naing, Nyi Nyi; Arfah, Nadiah Wan; Noorjan, KON; Kueh, Yee Cheng; Rasalingam, Kantha (IIUM Medical Journal Malaysia, 2020)
Introduction: Astrocytic gliomas are the most common and lethal intracranial brain tumours and rely on angiogenesis for the tumour development. Endothelial progenitor cells (EPCs) contribute to the angiogenesis of glioma tumour. Objectives: The study aimed to investigate the matured circulating endothelial cells population in the peripheral blood mononuclear cells (PBMCs) and its associations with tissue resident angiogenic cells in astrocytic glioma patients. Methods: A total of 22 astrocytic glioma patients were recruited from Hospital Universiti Sains Malaysia. Tumour were sliced and stained with CD133+ and VEGFA+ for angiogenic cells (n=22). The circulating (CD133-/VEGFR2+) matured endothelial cells in PBMCs (n=22) were quantified using FACS. The paired t-test and Pearson correlation test were used for the data analysis. Results: The angiogenic cells in brain tumour tissue were significantly higher compared to adjacent normal brain tissue (median 1.07±0.96% vs. median 0.69±0.68%; Wilcoxon signed rank test Z=-3.100; p=0.002). Positive correlation was found between the angiogenic cells of brain tumour tissue and adjacent normal brain tissue (Spearman’s rho correlation test, r=0.56; p=0.007). Significant positive correlation was found between matured endothelial cells in peripheral circulating systems and angiogenic cells in tumour of astrocytic glioma patients (Pearson correlation test, r=0.60, p=0.003).Conclusion:The findings of the study give support to the possible roles of EPCs in astrocytic glioma patients. Thus targeting tissue resident angiogenic cells and matured circulating endothelial cells by antiangiogenic treatment might be useful to prevent the tumour growth.